An unusual case of chronic lymphocytic leukemia with trisomy 12 and t(14;18) and a favorable response to ibrutinib. (2021) - Haddad, Fady Gh; Chebly, Alain; El Sett, Antoine; Kourie, Hampig Raphael; Farra, Chantal
Abstract: Chronic lymphocytic leukemia (CLL) is the most common type of adult leukemia. Chromosomal abnormalities are reported to play important roles in CLL pathogenesis and evolution, including deletions of 11q, 13q, 17p, and trisomy12, that are frequently observed and have a known prognostic value. Furthermore, the mutational status of the IGHV gene was reported as an independent prognostic marker in CLL impacting the choice of therapy. We herein, report an unusual presentation of a Lebanese CLL patient with two cytogenetic abnormalities: trisomy 12 and t(14;18)(q32;q21), along with an unmutated IGHV, displaying a favorable response to ibrutinib with a maintained complete remission.